Open‐Label Phase 1 Futility Studies of Salsalate and Young Plasma in Progressive Supranuclear Palsy. Issue 4 (10th April 2020) - VandeVrede, Lawren; Dale, Marian L.; Fields, Scott; Frank, Megan; Hare, Emma; Heuer, Hilary W.; Keith, Kellie; Koestler, Mary; Ljubenkov, Peter A.; McDermott, Dana; Ohanesian, Noelle; Richards, Jennifer; et al.
ABSTRACT: Background: Progressive supranuclear palsy (PSP) is a neurodegenerative disease without approved therapies, and therapeutics are often tried off‐label in the hope of slowing disease progression. Results from these experiences are seldom shared, which limits evidence‐based knowledge to guide future treatment decisions. Objectives: To describe an open‐label experience, including safety/tolerability, and longitudinal changes in biomarkers of disease progression in PSP‐Richardson's syndrome (PSP‐RS) patients treated with either salsalate or young plasma and compare to natural history data from previous multicenter studies. Methods: For 6 months, 10 PSP‐RS patients received daily salsalate 2, 250 mg, and 5 patients received monthly infusions of four units of young plasma. Every 3 months, clinical severity was assessed with the Progressive Supranuclear Palsy Rating Scale (PSPRS), and MRI was obtained for volumetric measurement of midbrain. A range of exploratory biomarkers, including cerebrospinal fluid levels of neurofilament light chain, were collected at baseline and 6 months. Interventional data were compared to historical PSP‐RS patients from the davunetide clinical trial and the 4‐Repeat Tauopathy Neuroimaging Initiative. Results: Salsalate and young plasma were safe and well tolerated. PSPRS change from baseline (mean ± standard deviation [SD]) was similar in salsalate (+5.6 ± 9.6), young plasma (+5.0 ± 7.1), and historical controls (+5.6 ± 7.1), and change in midbrain volume (cm 3  ± SD) did not differ between salsalate (–0.07 ± 0.03), young plasma (–0.06 ± 0.03), and historical controls (–0.06 ± 0.04). No differences were observed between groups on any exploratory endpoint. Conclusions: Neither salsalate nor young plasma had a detectable effect on disease progression in PSP‐RS. Focused open‐label clinical trials incorporating historical clinical, neuropsychological, fluid, and imaging biomarkers provide useful preliminary data about the promise of novel PSP‐directed therapies.